Acculturation of Hindu-Muslim Culture (Study of Rodat Dance - Ngaben Puri Pemecutan Ceremony, Denpasar Bali - Ida Ayu Tary Puspa; Ida Bagus Subrahmaniam Satya (International Journal of Interreligious and Intercultural Studies, 2023)
The existence of nyama selam in Bali is spread in several places such as Pegayaman, Gelgel, Kepaon, Serangan, Kampung Jawa, and Kecicang.There is room for them to live side by side with nyama Hindu. They interact with each other, but their respective cultures are still visible, but there is also a mutual culture that is embraced in strengthening the relationship between people for the harmony of the nation-state. megibung tradition as a characteristic of eating food together in one place according to Balinese tradition is also carried out by nyama selam Kepaon at the time of breaking the fast at the mosque. The unique acculturation is that there is also the Rodat Kepaon dance which is always present to fill the event when there is a Ngaben ceremony at Puri Pemecutan.The Rodat Kepaon dance is always present to fill the event when there is a Ngaben ceremony at Puri Pemecutan. Like at the Plebon/Ngaben Pemecutan King XI on January 21, 2022.Cultural acculturation is created through arts with ceremonies. As a form of acculturation, the Rodat Dance will appear in the first accompaniment, followed by the corpse of the Pemecutan King on the bade as a stretcher for the setra/grave. Rodat dancers wear uniforms like the navy with 2 men in red and followed by a line of other men wearing blue clothes and carrying swords. Their attractions are like playing silat. Of course, it will be interesting because if there is a Ngaben ceremony in Bali, what is commonly staged is The Baris Memedi dance or The Katekok Jago dance. However, Puri Pemecutan performs Rodat Kepaon Dance. This acculturation will reveal the forms of Hindu-Muslim culture and the meanings contained in the Rodat Dance-Ngaben Ceremony.